Vinyl acetate synthesis method, vinyl acetate catalyst synthesized by ethylene method and preparation method of vinyl acetate catalyst
By using a catalyst that supports Pd, Group IB metals and alkali metal acetate in the vinyl acetate synthesis process, the mass ratio of Pd2+/(Pd0+Pd2+) was controlled, and the problem of high ethylene acetate content in vinyl acetate synthesis was solved. , significantly improves the purity of the product.
Patent Information
- Application Number
- CN202310775668.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-28
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2043-06-28
AI Technical Summary
The by-product ethylene acetate content in the existing vinyl acetate synthesis process is relatively high, which affects product quality.
The catalyst supported by the carrier Pd, Group IB metal and alkali metal acetate was used to control the mass ratio of Pd2+/(Pd0+Pd2+) in the range of 10% to 45%, significantly reducing diacetic acid Impurity content of ethylene esters.
It effectively reduces the impurity content of ethylene diacetate during vinyl acetate synthesis and improves product purity.
Smart Images

Figure BDA0004309280040000131
Abstract
Description
Technical Field
[0001] The invention relates to a catalyst for synthesizing vinyl acetate by an ethylene process and a preparation method thereof, and a method for synthesizing vinyl acetate. Background Art
[0002] Vinyl acetate, also known as vinyl acetate or vinyl acetate, is a colorless, sweet and highly flammable liquid that can be dissolved in alcohols, benzene, ethers, acetone, and slightly soluble in water. Vinyl acetate is the precursor of polyvinyl acetate and ethylene-vinyl acetate copolymer, and is an important industrial polymer. Vinyl acetate can be used as an adhesive, a raw material for synthesizing vinylon as white glue, and producing coatings, etc. It has broad development space in the chemical field.
[0003] At present, the main method for producing vinyl acetate is to use ethylene, oxygen and acetic acid as raw materials, palladium-gold-potassium acetate / silicon dioxide as catalyst, and produce vinyl acetate, water and by-product carbon dioxide through gas phase catalytic reaction. It also produces trace amounts of ethyl acetate, acetaldehyde and other acetoxylated products.
[0004] US3743607 discloses a catalyst containing palladium, gold and alkali metal acetate. The catalyst is prepared by the following steps: impregnating a carrier, such as silicic acid, alumina, silicate or aluminum phosphate, with an aqueous solution of a palladium salt and a gold salt; evaporating the resulting mixture to dryness. Reducing the palladium salt and the gold salt to a metallic state with a reducing agent. The catalyst is then washed with water, impregnated with a sodium acetate solution and dried for use. The impurity content in this method is relatively high. Summary of the invention
[0005] The object of the present invention is to provide a vinyl acetate catalyst which can significantly reduce the impurity content of ethylene diacetate in the product.
[0006] To achieve the above-mentioned object, according to a first aspect of the present invention, there is provided a catalyst for synthesizing vinyl acetate by an ethylene process, comprising a carrier and Pd, a Group IB metal and an alkali metal acetate supported on the carrier, wherein an X-ray photoelectron spectroscopy (XPS) of the catalyst shows that Pd 2+ The content of the Pd state accounts for 10% to 45% of the total Pd element content, preferably 15-42%.
[0007] According to a second aspect of the present invention, there is provided a method for preparing a catalyst for synthesizing vinyl acetate by an ethylene process, the method comprising:
[0008] (a) immersing a catalyst support source in a solution containing a Pd source and a Group IB metal source, and drying to prepare a precursor I;
[0009] (b) mixing and contacting the precursor I with a solution of a basic compound, and drying to obtain the precursor II;
[0010] (c) reducing the precursor II with a reducing agent, washing with water, and drying to obtain the precursor III;
[0011] (d) immersing the precursor III in a solution containing a Pd source and drying to prepare the precursor IV;
[0012] (e) impregnating the precursor IV with alkali metal acetate and drying to obtain a finished catalyst.
[0013] According to a third aspect of the present invention, a catalyst prepared by the preparation method of the present invention is provided.
[0014] According to a fourth aspect of the present invention, a method for synthesizing vinyl acetate is provided, wherein a raw gas for synthesizing vinyl acetate is subjected to a gas-phase catalytic synthesis reaction in the presence of a catalyst, wherein the catalyst comprises the catalyst of the present invention.
[0015] The Pd 2+ / (Pd 0 +Pd 2+ ) mass ratio characteristics, can significantly reduce the impurity content of ethylene diacetate in the product.
[0016] The vinyl acetate catalyst of the present invention mainly solves the problem of high content of ethylene diacetate as a byproduct in the process of synthesizing vinyl acetate by ethylene gas phase method. The present invention adopts a vinyl acetate catalyst, including a carrier and Pd, a first subgroup metal and an alkali metal acetate loaded on the carrier, wherein the Pd in the X-ray photoelectron spectrum of the catalyst is 2+ The content of ethylene diacetate is in the range of 10% to 45%, preferably 15-42%, so that the catalyst can effectively reduce the content of ethylene diacetate in the product. DETAILED DESCRIPTION
[0017] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0018] In the present invention, Pd 2+ / (Pd 0 +Pd 2+ The mass ratio of Pd and Pd is calculated by using the peak area of XPS. 0 With Pd 2+ The amount.
[0019] In the present invention, the composition of each substance in the catalyst is calculated based on the input materials.
[0020] The present invention provides a catalyst for synthesizing vinyl acetate by ethylene process, comprising a carrier and Pd, IB group metal and alkali metal acetate loaded on the carrier, wherein the X-ray photoelectron spectrum (XPS) of the catalyst shows that Pd 2+ The content of the Pd state accounts for 10% to 45% of the total Pd element content, preferably 15-42%. 2+ / (Pd 0 +Pd 2+ ) mass ratio characteristics, can significantly reduce the impurity content of ethylene diacetate in the product.
[0021] In the present invention, the Group IB metal in the catalyst exists in the form of a simple substance and / or an oxide.
[0022] In the present invention, Pd exists in the form of a simple substance and / or an oxide.
[0023] According to a preferred embodiment of the present invention, in the catalyst, Pd 0 The content of ethylene diacetate is 1-12 g / L, preferably 2-3 g / L, for example, 2.1 g / L, 2.2 g / L, 2.3 g / L, 2.4 g / L, 2.5 g / L, 2.6 g / L, 2.7 g / L, 2.8 g / L, 2.9 g / L, 3 g / L. This can significantly reduce the impurity content of ethylene diacetate in the product.
[0024] According to a preferred embodiment of the present invention, the amount of Group IB metal in the catalyst, calculated as element, is 0.1 to 10 g / L, preferably 0.4 to 0.8 g / L, for example 0.4 g / L, 0.5 g / L, 0.6 g / L, 0.7 g / L, 0.8 g / L. This can significantly reduce the impurity content of ethylene diacetate in the product.
[0025] According to a preferred embodiment of the present invention, the content of alkali metal acetate is 10-100 g / L, preferably 20-40 g / L, for example 20 g / L, 30 g / L, 40 g / L, thereby significantly reducing the impurity content of ethylene diacetate in the product.
[0026] According to a preferred embodiment of the present invention, all Group IB metals can be used in the present invention. For the present invention, the Group IB metal is preferably Au and / or Cu, preferably Au. This can significantly reduce the impurity content of ethylene diacetate in the product.
[0027] According to a preferred embodiment of the present invention, the alkali metal element is selected from one or more of Li, Na, K, Rb, Cs, and Fr, preferably one or more of Na and K; preferably, the alkali metal acetate is potassium acetate; thereby, the impurity content of ethylene diacetate in the product can be significantly reduced.
[0028] In the present invention, there is no special requirement for the carrier, and the commonly used carriers in the art can achieve the purpose of the present invention. According to a preferred embodiment of the present invention, the carrier is selected from one or more of silicon oxide and aluminum oxide. According to a preferred embodiment of the present invention, preferably, the carrier is selected from spherical silicon dioxide, and preferably the diameter of the spherical silicon dioxide is 2-8 mm, and the specific surface area is 150-200 m 2 / g, pore volume is 0.6-1cm 3 / g.
[0029] The catalysts having the above-mentioned characteristics of the present invention can achieve the purpose of the present invention, and there is no special requirement for the preparation method thereof. According to the present invention, a preparation method of a catalyst for synthesizing vinyl acetate by an ethylene process is provided, and the method comprises: (a) immersing a catalyst support source in a solution containing a Pd source and a Group IB metal source, and drying to prepare a precursor I;
[0030] (b) mixing and contacting the precursor I with a solution of a basic compound, and drying to obtain the precursor II;
[0031] (c) reducing the precursor II with a reducing agent, washing with water, and drying to obtain the precursor III;
[0032] (d) immersing the precursor III in a solution containing a Pd source and drying to prepare the precursor IV;
[0033] (e) impregnating the precursor IV with alkali metal acetate and drying to obtain a finished catalyst.
[0034] According to a preferred embodiment of the present invention, the X-ray photoelectron spectroscopy (XPS) of the prepared catalyst shows that Pd 2+ The content of the Pd state accounts for 10% to 45% of the total Pd element content, preferably 15-42%; thereby, the impurity content of ethylene diacetate in the product can be significantly reduced.
[0035] According to a preferred embodiment of the present invention, in the prepared catalyst, the content of Pd0, calculated as an element, is 1 to 12 g / L, preferably 2 to 3 g / L; thereby, the impurity content of ethylene diacetate in the product can be significantly reduced.
[0036] According to a preferred embodiment of the present invention, in the prepared catalyst, the amount of Group IB metal, calculated as element, is 0.1 to 10 g / L, preferably 0.4 to 0.8 g / L; thereby, the impurity content of ethylene diacetate in the product can be significantly reduced.
[0037] According to a preferred embodiment of the present invention, the content of alkali metal acetate in the prepared catalyst is 10-100 g / L, preferably 20-40 g / L, thereby significantly reducing the impurity content of ethylene diacetate in the product.
[0038] According to a preferred embodiment of the present invention, all Group IB metals can be used in the present invention. According to a preferred embodiment of the present invention, the Group IB metal is Au and / or Cu, preferably Au. This can significantly reduce the impurity content of ethylene diacetate in the product.
[0039] According to a preferred embodiment of the present invention, the alkali metal element is selected from one or more of Li, Na, K, Rb, Cs, and Fr, preferably one or more of Na and K; preferably, the alkali metal acetate is potassium acetate.
[0040] In the present invention, there is no special requirement for the carrier source, and the commonly used carrier sources in the art can achieve the purpose of the present invention. The present invention has no special requirements for this. The carrier source is selected from one or more of silicon dioxide and aluminum oxide; preferably, the carrier source is selected from spherical silicon dioxide, and preferably the diameter of the spherical silicon dioxide is 2-8 mm, and the specific surface area is 150-200 m 2 / g, pore volume is 0.6-1cm 3 / g.
[0041] In the present invention, the alkaline compound can be selected from a wide range of types. According to a preferred embodiment of the present invention, in step (b), the alkaline compound includes but is not limited to one or more of sodium silicate and sodium hydroxide.
[0042] According to a preferred embodiment of the present invention, in step (c), the reducing agent includes but is not limited to one or more of hydrazine hydrate and sodium citrate.
[0043] According to a preferred embodiment of the present invention, the conditions in step (a) include: a solid-liquid volume ratio of 1:1-1:1.2, a Pd content of 1 to 12 g / L, preferably 2 to 3 g / L, in the solution containing a Pd source and a Group IB metal source, calculated as an element; and a Group IB metal content of 0.1 to 10 g / L, preferably 0.4 to 0.8 g / L.
[0044] According to a preferred embodiment of the present invention, the conditions in step (b) include: a solid-liquid volume ratio of 1:1-1.2, and a concentration of the solution of the alkaline compound of 10-30% by weight.
[0045] In the present invention, there are no special requirements for the reduction, water washing and drying conditions. Common reduction, water washing and drying conditions can be used in the present invention. According to a preferred embodiment of the present invention, the conditions in step (c) include: reduction time of 1-10 hours; water washing time of 1-20 hours; drying temperature of 60-100° C.; drying time of 1-10 hours.
[0046] According to a preferred embodiment of the present invention, the conditions in step (d) include: a solid-liquid volume ratio of 1:1-1.2, and a Pd content in the solution of 0.5-2 g / L.
[0047] According to a preferred embodiment of the present invention, preferably, step (d) is carried out in the presence of acetic acid, and the amount of acetic acid used is 1-10 g / L solid, preferably 5-8 g / L solid.
[0048] According to a preferred embodiment of the present invention, the conditions in step (e) include: drying temperature of 60-100° C.; and drying time of 1-10 hours.
[0049] In the present invention, in steps (a) to (e), the process is allowed to stand as required in order to allow the solid and the liquid to fully contact each other.
[0050] In the present invention, step (a) can be optionally allowed to stand for 0.5-3 hours as required.
[0051] In the present invention, step (b) can be optionally allowed to stand for 12-24 hours as required.
[0052] In the present invention, step (c) can be optionally allowed to stand for 3-6 hours as required.
[0053] In the present invention, step (d) can be optionally allowed to stand for 3-6 hours as required.
[0054] In the present invention, step (e) can be optionally allowed to stand for 3-6 hours as required.
[0055] The present invention provides a catalyst prepared by the preparation method of the present invention.
[0056] The present invention provides a method for synthesizing vinyl acetate. In the presence of a catalyst, raw gas for synthesizing vinyl acetate undergoes a gas-phase catalytic synthesis reaction. The catalyst includes the catalyst of the present invention.
[0057] According to a preferred embodiment of the present invention, the raw gas for synthesizing vinyl acetate includes oxygen, ethylene, nitrogen and acetic acid; preferably, the raw gas composition in a molar ratio is oxygen:ethylene:nitrogen:acetic acid=1:(5-7):(4-8):(1-2).
[0058] According to a preferred embodiment of the present invention, the conditions for the gas phase catalytic synthesis reaction include: the reaction pressure is 0.5 to 0.9 MPa.
[0059] According to a preferred embodiment of the present invention, the conditions for the gas phase catalytic synthesis reaction include: a reaction temperature of 130 to 200°C.
[0060] According to a preferred embodiment of the present invention, the conditions for the gas phase catalytic synthesis reaction include: the raw gas volume space velocity is 1600 to 3000 hr -1 .
[0061] In the present invention, unless otherwise specified, the operation is carried out at room temperature.
[0062] In the present invention, unless otherwise specified, the solvent of the solution is water.
[0063] In the present invention, the content of each component in the catalyst is tested by: the content of elements in different valence states is represented by the peak area of the XPS spectrum, and the peak area ratio can represent the ratio of the content of elements in different valence states.
[0064] Example 1
[0065] 1. Catalyst preparation
[0066] (a) Take 1100 ml of spherical silica carrier (diameter 5 mm, specific surface area 175 m 2 / g, pore volume is 0.8cm 3 / g) was immersed in a mixed aqueous solution of chloropalladic acid and chloroauric acid, and the solid-liquid volume ratio was calculated as 1:1.2, wherein the content of palladium (calculated as element, the same below) in the solution used was 2.75 g / L, and the content of gold (calculated as element, the same below) was 0.625 g / L, and the catalyst precursor I was prepared by drying at 80° C. for 30 minutes;
[0067] (b) adding 100 ml of sodium silicate aqueous solution (27.5 g of Na2SiO3·9H2O is prepared into 100 ml of aqueous solution) with a solid-liquid volume ratio of 1:1.2; mixing well and letting stand for 24 hours, and then drying at 80°C for 8 hours to obtain catalyst precursor II;
[0068] (c) adding 60 g of 85% wt hydrazine hydrate for reduction, standing for 4 hours, then washing with deionized water, and drying at 100° C. for 6 hours to obtain catalyst precursor III;
[0069] (d) immersing the catalyst precursor III in a chloropalladic acid aqueous solution, with a solid-liquid volume ratio of 1:1.2, wherein the palladium content in the solution used is 0.50 g / L, mixing well and standing for 6 hours, and then drying at 80° C. for 12 hours to prepare a catalyst precursor IV;
[0070] (e) The catalyst precursor IV was immersed in a potassium acetate aqueous solution and dried at 80° C. for 6 hours to obtain a finished catalyst, wherein the potassium acetate content in the catalyst was 30 g / L.
[0071] 2. Catalyst evaluation
[0072] The fixed bed reactor was used for evaluation, and the specific conditions were:
[0073] Catalyst filling volume: 40ml;
[0074] The composition of the reaction raw materials (by molar ratio): oxygen: ethylene: nitrogen: acetic acid = 1: 6.8: 7.2: 1.7;
[0075] Reaction raw material feed volume space velocity: 2000hr -1 ;
[0076] Reaction pressure: 0.7MPa;
[0077] Reaction temperature: 135°C;
[0078] Reaction time: 100hr;
[0079] The content of each component in the reaction product was analyzed by gas chromatography, and then the space-time yield of the catalyst was calculated.
[0080] For the convenience of comparison, the experimental results are listed in Table 1.
[0081] Example 2
[0082] 1. Catalyst preparation
[0083] (a) Take 1100 ml of spherical silica carrier (diameter 5 mm, specific surface area 175 m 2 / g, pore volume is 0.8cm 3 / g) was immersed in a mixed aqueous solution of chloropalladic acid and chloroauric acid, calculated according to a solid-liquid volume ratio of 1:1.2, wherein the content of palladium in the solution used was 2.75 g / L and the content of gold was 0.625 g / L, and the catalyst precursor I was prepared by drying at 80° C. for 30 minutes;
[0084] (b) adding 100 ml of sodium silicate aqueous solution (27.5 g of Na2SiO3·9H2O is prepared into 100 ml of aqueous solution) with a solid-liquid volume ratio of 1:1.2; mixing well and letting stand for 24 hours, and then drying at 80°C for 8 hours to obtain catalyst precursor II;
[0085] (c) adding 60 g of 85% wt hydrazine hydrate for reduction, standing for 4 hours, then washing with deionized water, and drying at 100° C. for 6 hours to obtain catalyst precursor III;
[0086] (d) immersing the catalyst precursor III in a chloropalladic acid aqueous solution, with a solid-liquid volume ratio of 1:1.2, wherein the palladium content in the solution used is 0.92 g / L, mixing well and standing for 6 hours, and then drying at 80° C. for 12 hours to prepare a catalyst precursor IV;
[0087] (e) The catalyst precursor IV was immersed in a potassium acetate aqueous solution and dried at 80° C. for 6 hours to obtain a finished catalyst, wherein the potassium acetate content in the catalyst was 30 g / L.
[0088] 2. Catalyst evaluation
[0089] The catalyst evaluation method was the same as in Example 1.
[0090] For the convenience of comparison, the experimental results are listed in Table 1.
[0091] Example 3
[0092] 1. Catalyst preparation
[0093] (a) Take 1100 ml of spherical silica carrier (diameter 5 mm, specific surface area 175 m 2 / g, pore volume is 0.8cm 3 / g) was immersed in a mixed aqueous solution of chloropalladic acid and chloroauric acid, and allowed to stand for 3 hours. The solid-liquid volume ratio was calculated to be 1:1.2, wherein the palladium content in the solution used was 2.75 g / L and the gold content was 0.625 g / L. The drying conditions included: drying at 80° C. for 30 minutes to prepare a catalyst precursor I;
[0094] (b) adding 100 ml of sodium silicate aqueous solution (27.5 g of Na2SiO3·9H2O is prepared into 100 ml of aqueous solution) with a solid-liquid volume ratio of 1:1.2; mixing well and letting stand for 24 hours, and then drying at 80°C for 8 hours to obtain catalyst precursor II;
[0095] (c) adding 60 g of 85% wt hydrazine hydrate for reduction, standing for 4 hours, then washing with deionized water, and drying at 100° C. for 6 hours to obtain catalyst precursor III;
[0096] (d) immersing the catalyst precursor III in an aqueous solution of chloropalladic acid, wherein the solid-liquid volume ratio is 1:1.2, wherein the palladium content in the solution used is 1.18 g / L, mixing well, standing for 6 hours, and then drying at 80° C. for 12 hours to prepare a catalyst precursor IV;
[0097] (e) The catalyst precursor IV was immersed in a potassium acetate aqueous solution and dried at 80° C. for 6 hours to obtain a finished catalyst, wherein the potassium acetate content in the catalyst was 30 g / L.
[0098] 2. Catalyst evaluation
[0099] The catalyst evaluation method was the same as in Example 1.
[0100] For the convenience of comparison, the experimental results are listed in Table 1.
[0101] Example 4
[0102] 1. Catalyst preparation
[0103] (a) Take 1100 ml of spherical silica carrier (diameter 5 mm, specific surface area 175 m 2 / g, pore volume is 0.8cm 3 / g) was immersed in a mixed aqueous solution of chloropalladic acid and chloroauric acid, calculated according to a solid-liquid volume ratio of 1:1.2, wherein the content of palladium in the solution used was 2.75 g / L and the content of gold was 0.625 g / L, and the catalyst precursor I was prepared by drying at 80° C. for 30 minutes;
[0104] (b) adding 100 ml of sodium silicate aqueous solution (27.5 g of Na2SiO3·9H2O is prepared into 100 ml of aqueous solution) with a solid-liquid volume ratio of 1:1.2; mixing well and letting stand for 24 hours, and then drying at 80°C for 8 hours to obtain catalyst precursor II;
[0105] (c) adding 60 g of 85% wt hydrazine hydrate for reduction, standing for 4 hours, then washing with deionized water, and drying at 100° C. for 6 hours to obtain catalyst precursor III;
[0106] (d) immersing the catalyst precursor III in a chloropalladic acid aqueous solution, with a solid-liquid volume ratio of 1:1.2, wherein the palladium content in the solution used is 2.0 g / L, mixing well and standing for 6 hours, and then drying at 80° C. for 12 hours to prepare a catalyst precursor IV;
[0107] (e) The catalyst precursor IV was immersed in a potassium acetate aqueous solution and dried at 80° C. for 6 hours to obtain a finished catalyst, wherein the potassium acetate content in the catalyst was 30 g / L.
[0108] 2. Catalyst evaluation
[0109] The catalyst evaluation method was the same as in Example 1.
[0110] For the convenience of comparison, the experimental results are listed in Table 1.
[0111] Example 5
[0112] The method of Example 1 was followed, except that 6 g of acetic acid was added to the solution in step (d).
[0113] Comparative Example 1
[0114] 1. Catalyst preparation
[0115] (a) Take 1100 ml of spherical silica carrier (diameter 5 mm, specific surface area 175 m 2 / g, pore volume is 0.8cm 3 / g) was immersed in a mixed aqueous solution of chloropalladic acid and chloroauric acid, calculated according to a solid-liquid volume ratio of 1:1.2, wherein the content of palladium in the solution used was 2.75 g / L, and the content of gold was 0.625 g / L, and the drying conditions included: drying at 80° C. for 30 minutes to prepare a catalyst precursor I;
[0116] (b) adding 100 ml of sodium silicate aqueous solution (27.5 g of Na2SiO3·9H2O is prepared into 100 ml of aqueous solution) with a solid-liquid volume ratio of 1:1.2; mixing well and letting stand for 24 hours, and then drying at 80°C for 8 hours to obtain catalyst precursor II;
[0117] (c) adding 60 g of 85% wt hydrazine hydrate for reduction, standing for 4 hours, then washing with deionized water, and drying at 100° C. for 6 hours to obtain catalyst precursor III;
[0118] (d) The catalyst precursor III was impregnated with an aqueous solution of potassium acetate and dried at 80° C. for 6 hours to obtain a finished catalyst, wherein the potassium acetate content in the catalyst was 30 g / L.
[0119] 2. Catalyst evaluation
[0120] The catalyst evaluation method was the same as in Example 1.
[0121] For the convenience of comparison, the experimental results are listed in Table 1.
[0122] Comparative Example 2
[0123] 1. Catalyst preparation
[0124] (a) Take 1100 ml of spherical silica carrier (diameter 5 mm, specific surface area 175 m 2 / g, pore volume is 0.8cm 3 / g) was immersed in a mixed aqueous solution of chloropalladic acid and chloroauric acid, calculated according to a solid-liquid volume ratio of 1:1.2, wherein the content of palladium in the solution used was 1g / L, and the content of gold was 0.1g / L, and the drying conditions included: drying at 80°C for 30 minutes to prepare a catalyst precursor I;
[0125] (b) adding 100 ml of sodium silicate aqueous solution (27.5 g of Na2SiO3·9H2O is prepared into 100 ml of aqueous solution) with a solid-liquid volume ratio of 1:1.2; mixing well and letting stand for 24 hours, and then drying at 80°C for 8 hours to obtain catalyst precursor II;
[0126] (c) adding 60 g of 85% wt hydrazine hydrate for reduction, standing for 4 hours, then washing with deionized water, and drying at 100° C. for 6 hours to obtain catalyst precursor III;
[0127] (d) immersing the catalyst precursor III in a chloropalladic acid aqueous solution, with a solid-liquid volume ratio of 1:1.2, wherein the palladium content in the solution used is 0.92 g / L, mixing well and standing for 6 hours, and then drying at 80° C. for 12 hours to prepare a catalyst precursor IV;
[0128] (e) The catalyst precursor IV was immersed in a potassium acetate aqueous solution and dried at 80° C. for 6 hours to obtain a finished catalyst, wherein the potassium acetate content in the catalyst was 30 g / L.
[0129] 2. Catalyst evaluation
[0130] The catalyst evaluation method was the same as in Example 1.
[0131] For the convenience of comparison, the experimental results are listed in Table 1.
[0132] Comparative Example 3
[0133] 1. Catalyst preparation
[0134] (a) Take 1100 ml of spherical silica carrier (diameter 5 mm, specific surface area 175 m 2 / g, pore volume is 0.8cm 3 / g) was immersed in a mixed aqueous solution of chloropalladic acid and chloroauric acid, calculated according to a solid-liquid volume ratio of 1:1.2, wherein the content of palladium in the solution used was 12 g / L, and the content of gold was 10 g / L, and the drying conditions included: drying at 80° C. for 30 minutes to prepare a catalyst precursor I;
[0135] (b) adding 100 ml of sodium silicate aqueous solution (27.5 g of Na2SiO3·9H2O is prepared into 100 ml of aqueous solution) with a solid-liquid volume ratio of 1:1.2; mixing well and letting stand for 24 hours, and then drying at 80°C for 8 hours to obtain catalyst precursor II;
[0136] (c) adding 60 g of 85% wt hydrazine hydrate for reduction, standing for 4 hours, then washing with deionized water, and drying at 100° C. for 6 hours to obtain catalyst precursor III;
[0137] (d) immersing the catalyst precursor III in a chloropalladic acid aqueous solution, with a solid-liquid volume ratio of 1:1.2, wherein the palladium content in the solution used is 0.92 g / L, mixing well and standing for 6 hours, and then drying at 80° C. for 12 hours to prepare a catalyst precursor IV;
[0138] (e) The catalyst precursor IV was immersed in a potassium acetate aqueous solution and dried at 80° C. for 6 hours to obtain a finished catalyst, wherein the potassium acetate content in the catalyst was 30 g / L.
[0139] 2. Catalyst evaluation
[0140] The catalyst evaluation method was the same as in Example 1.
[0141] For the convenience of comparison, the experimental results are listed in Table 1.
[0142] Table 1
[0143]
[0144] STY refers to the space-time yield of vinyl acetate, which is calculated as:
[0145] STY(t / dm 3 )=86*ethylene consumption (mol / d)*1000 / catalyst dosage (m 3 )
[0146] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A catalyst for synthesizing vinyl acetate from ethylene, characterized in that: The catalyst comprises a carrier and Pd, IB group metal and alkali metal acetate loaded on the carrier, wherein the X-ray photoelectron spectrum of the catalyst shows that Pd 2+ The content of the Pd state accounts for 10% to 45% of the total Pd element content, preferably 15-42%.
2. The catalyst according to claim 1, wherein In the catalyst, Pd 0 The content of is 1 to 12 g / L, preferably 2 to 3 g / L; and / or The catalyst contains 0.1 to 10 g / L, preferably 0.4 to 0.8 g / L, of Group IB metal, calculated as the element; and / or The content of alkali metal acetate in the catalyst is 10 to 100 g / L, preferably 20 to 40 g / L.
3. The catalyst according to claim 1 or 2, wherein The IB group metal is Au and / or Cu, preferably Au; and / or The alkali metal element is selected from one or more of Li, Na, K, Rb, Cs and Fr, preferably one or more of Na and K; preferably, the alkali metal acetate is potassium acetate; and / or The carrier is selected from one or more of silicon oxide and aluminum oxide; Preferably, the carrier is selected from spherical silica, preferably the diameter of the spherical silica is 2-8 mm and the specific surface area is 150-200 m 2 / g, pore volume is 0.6-1cm 3 / g.
4. A method for preparing a catalyst for synthesizing vinyl acetate by ethylene process, characterized in that: The method includes: (a) immersing a catalyst support source in a solution containing a Pd source and a Group IB metal source, and drying to prepare a precursor I; (b) mixing and contacting the precursor I with a solution of a basic compound, and drying to obtain the precursor II; (c) reducing the precursor II with a reducing agent, washing with water, and drying to obtain the precursor III; (d) immersing the precursor III in a solution containing a Pd source and drying to prepare the precursor IV; (e) impregnating the precursor IV with alkali metal acetate and drying to obtain a finished catalyst.
5. The preparation method according to claim 4, wherein X-ray photoelectron spectroscopy of the prepared catalyst showed that Pd 2+ The content of the Pd state accounts for 10% to 45% of the total Pd element content, preferably 15-42%; and / or In the prepared catalyst, Pd 0 The content of is 1 to 12 g / L, preferably 2 to 3 g / L; and / or In the prepared catalyst, the content of Group IB metal is 0.1 to 10 g / L, preferably 0.4 to 0.8 g / L, calculated as the element; and / or In the prepared catalyst, the content of alkali metal acetate is 10-100 g / L, preferably 20-40 g / L.
6. The preparation method according to claim 4 or 5, wherein: The Group IB metal is Au and / or Cu, preferably Au; and / or The alkali metal element is selected from one or more of Li, Na, K, Rb, Cs and Fr, preferably one or more of Na and K; preferably, the alkali metal acetate is potassium acetate; and / or In step (a), the carrier source is selected from one or more of silicon dioxide and aluminum oxide; Preferably, the carrier source is selected from spherical silica, preferably the diameter of the spherical silica is 2-8 mm and the specific surface area is 150-200 m 2 / g, pore volume is 0.6-1cm 3 / g; and / or In step (b), the alkaline compound is selected from one or more of sodium silicate and sodium hydroxide; and / or In step (c), the reducing agent is selected from one or more of hydrazine hydrate and sodium citrate.
7. The preparation method according to any one of claims 4 to 6, wherein: The conditions in step (a) include: a solid-liquid volume ratio of 1:1-1.2, a Pd content of 1 to 12 g / L, preferably 2 to 3 g / L, in the solution containing a Pd source and a Group IB metal source, calculated as an element; a Group IB metal content of 0.1 to 10 g / L, preferably 0.4 to 0.8 g / L; and / or The conditions in step (b) include: a solid-liquid volume ratio of 1:1-1.2, and a concentration of the solution of the basic compound of 10-30 wt %; The conditions in step (d) include: a solid-liquid volume ratio of 1:1-1.2, and a Pd content in the solution of 0.5-2 g / L; Preferably, step (d) is carried out in the presence of acetic acid, and the amount of acetic acid used is 1-10 g / L solid, preferably 5-8 g / L solid.
8. The catalyst prepared by the preparation method according to any one of claims 4 to 7.
9. A method for synthesizing vinyl acetate, wherein the raw material gas for synthesizing vinyl acetate is subjected to a gas phase catalytic synthesis reaction in the presence of a catalyst, characterized in that: The catalyst comprises the catalyst according to any one of claims 1 to 3 and 8.
10. The synthesis method according to claim 9, wherein The raw gas for synthesizing vinyl acetate includes oxygen, ethylene, nitrogen and acetic acid; preferably, In terms of molar ratio, the molar ratio of oxygen, ethylene, nitrogen and acetic acid is 1:(5-7):(4-8):(1-2); and / or The conditions for the gas phase catalytic synthesis reaction include: The reaction pressure is 0.5-0.9 MPa, and / or The reaction temperature is 130-200°C, and / or The raw gas volume space velocity is 1600~3000hr -1 .
Citation Information
Patent Citations
Palladium-gold catalyst vinyl acetate production
CA2258686A1
Vinyl acetate synthesis method
CN115246771A
Method for preparing 1, 4-diacetoxy-2-butene
CN115466177A
Method of manufacturing epitaxial silicon wafers
KR102139435B1
Hydrogenation catalyst
WO2011113881A2
